2020
DOI: 10.3390/jmse8070502
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Structure of the Kuroshio Extension Front in Spring 2019

Abstract: Satellite data products and high-resolution in situ observations were combined to investigate the evolution and structure of the Kuroshio Extension Front in Spring 2019. The former reveals the variation of the front is influenced by the northward movement of the Kuroshio Extension through transporting warm and saline water to a cold and brackish water region. The latter indicates steep upward slopes of the isopycnals, tilting northward in the frontal zone, as well as several ~300 m thick blobs of North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Regarding width prediction, accuracy (1 km) typically exceeded 60%, while accuracy (3 km) consistently went beyond 80%. Remarkably, the highest accuracy was observed when the sound source directed southward, aligning with the KEF's near parallelism to the latitude line and its northward inclination (Wang et al, 2020). This study strategically positioned the sound source cloth at the critical KEF location, significantly enhancing model interpretability.…”
Section: Comparison Of Three-dimensional Prediction Resultsmentioning
confidence: 82%
“…Regarding width prediction, accuracy (1 km) typically exceeded 60%, while accuracy (3 km) consistently went beyond 80%. Remarkably, the highest accuracy was observed when the sound source directed southward, aligning with the KEF's near parallelism to the latitude line and its northward inclination (Wang et al, 2020). This study strategically positioned the sound source cloth at the critical KEF location, significantly enhancing model interpretability.…”
Section: Comparison Of Three-dimensional Prediction Resultsmentioning
confidence: 82%
“…The investigated relationship between eddies and SST gradients focuses only on the ocean surface due to the limitation of remotely sensed data (Ritchie et al, 2003). The vertical structure of eddies can reach a depth of 160 meters (Sun et al, 2019), and the depth of the front can reach more than 300 m (Wang et al, 2020). Thus, the entire structure of eddies and fronts is not fully incorporated in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the SST gradient, which is used as a proxy for fronts (Xi et al, 2022), few studies have investigated the influence of eddies on modulating the SST gradient. For instance, Wang et al (2020) revealed that eddies in the KE region can carry the front as they move westward and that the front gradually weakens. The eddies can expand the region with a large SST gradient in the preexisting frontal zone (Yuan and Castelao, 2017).…”
Section: Introductionmentioning
confidence: 99%